Discriminability of Single and Multichannel Intracortical Microstimulation within Somatosensory Cortex - Cynthia Kay Overstreet; Randall Blake Hellman; Ruben Ponce Wong; Veronica J. Santos; Stephen Helms Tillery (Frontiers in Bioengineering and Biotechnology, 2016)
The addition of tactile and proprioceptive feedback to neuroprosthetic limbs is expected to significantly improve the control of these devices. Intracortical microstimulation (ICMS) of somatosensory cortex is a promising method of delivering this sensory feedback. To date, the main focus of somatosensory ICMS studies has been to deliver discriminable signals, corresponding to varying intensity, to a single location in cortex. However, multiple independent and simultaneous streams of sensory information will need to be encoded by ICMS to provide functionally relevant feedback for a neuroprosthetic limb (e.g. encoding contact events and pressure on multiple digits).In this study, we evaluated the ability of an awake, behaving non-human primate (Macaca mulatta) to discriminate ICMS stimuli delivered on multiple electrodes spaced within somatosensory cortex. We delivered serial stimulation on single electrodes to evaluate the discriminability of sensations corresponding to ICMS of distinct cortical locations. Additionally, we delivered trains of multichannel stimulation, derived from a tactile sensor, synchronously across multiple electrodes. Our results indicate that discrimination of multiple ICMS stimuli is a challenging task, but that discriminable sensory percepts can be elicited by both single and multichannel ICMS on electrodes spaced within somatosensory cortex.